Pathologies elicited by the gymnophallid metacercariae of Bartolius pierrei in the clam Darina solenoides - Cremonte, Florencia (2003)
Darina solenoides (Mactridae), a common intertidal bivalve in the Argentine Patagonian coast, serves as both first and second intermediate host for the gymnophallid Bartolius pierrei (Trematoda: Digenea). Cercariae enter the clams actively by piercing the mantle border; young metacercariae ascend along the space between the outer mantle epithelium and shell and they settle in the dorsal general extrapallial space just ahead the posterior adductor muscle. Host reaction comprises mantle tissues alterations (hyperplasia and metaplasia) leading to the encapsulation of the metacercariae by the formation of a one-cell-layer thick sac, which progressively detaches from the mantle epithelium. Sacs containing fully developed metacercariae, which are surrounded by a hyaline non-cellular envelope, become internal and are found in the postero-dorsal region of the visceral mass. Two sacs usually containing from two to 44 metacercariae, one at each side of the clam, were observed. In some cases, in which the infection seems not to proceed as usual, dead and dying metacercariae and their debris were found in the same position within the extrapallial space where the host reaction usually starts. In these cases, the mantle reaction is accompanied by an inner shell surface alteration consisting of calcium carbonate deposits partially surrounding the reaction complex or other abnormal calcifications in the form of loose mineral concretions.